The Writing Tables of James Roberts. (23rd February 2019) - Jowett, John
Abstract: This paper examines the pivotal role of James Roberts in the manufacture of writing tables in the years between 1579 and 1602. These were small books that easily slipped into the pocket, amphibious in form as they combined erasable blank leaves for note-taking with print matter of a kind that fell under the generic heading of almanacs. The writing tables were originally issued by the manufacturer of the reusable leaves Frank Adams, but then were wrested from his control by Roberts and his partner Richard Watkins. When Roberts's patent on the printing of all almanacs and prognostications came to an end, control reverted to the paper-maker's successor, Robert Triplet. A key characteristic of this episode lies in the peculiar role of the printer with respect to patent-protected books. The key point from the more immediate perspective of Roberts lies in his rise to and fall from overall control of the manufacture and publication of writing tables.